Atypical centrioles are present in Tribolium sperm. Issue 3 (15th March 2017) - Fishman, E. L.; Jo, Kyoung; Ha, Andrew; Royfman, Rachel; Zinn, Ashtyn; Krishnamurthy, Malathi; Avidor-Reiss, Tomer
Abstract : Abstract : Typical centrioles are made of microtubules organized in ninefold symmetry. Most animal somatic cells have two centrioles for normal cell division and function. These centrioles originate from the zygote, but because the oocyte does not provide any centrioles, it is surprising that the zygotes of many animals are thought to inherit only one centriole from the sperm. Recently, in the sperm of Drosophila melanogaster, we discovered a second centriolar structure, the proximal centriole-like structure (PCL), which functions in the zygote. Whether the sperm of other insects has a second centriolar structure is unknown. Here, we characterized spermiogenesis in the red flour beetle, Tribolium castaneum . Electron microscopy suggests that Tribolium has one microtubule-based centriole at the tip of the axoneme and a structure similar to the PCL, which lacks microtubules and lies in a cytoplasmic invagination of the nucleus. Immunostaining against the orthologue of the centriole/PCL protein, Ana1, also recognizes two centrioles near the nucleus during spermiogenesis: one that is microtubule-based at the tip of the axoneme, suggesting it is the centriole; and another that is more proximal and appears during early spermiogenesis, suggesting it is the PCL. Together, these findings suggest that Tribolium sperm has one microtubule-based centriole and one microtubule-lacking centriole.